Subjective and objective indicators affecting satisfaction of internal affairs employees with their professional service activities - A.S. Dushkin; M.G. Barinova; I.N. Konopleva; E.V. Dushkina (Психология и право)
Context and relevance. Satisfaction of internal affairs employees with their professional service activities is an important component in the system of staffing as well as moral and psychological support of the activities of internal affairs bodies of the Russian Federation. Objective. To determine the subjective and objective indicators that affect the satisfaction of internal affairs employees with their professional service activities. Hypothesis. Satisfaction of internal affairs employees with their professional service activities is affected by both subjective and objective indicators. Methods and materials. The respondents were 124 employees of the territorial bodies of the Ministry of Internal Affairs of Russia. The research methods were represented by the following diagnostic block: “Diagnostics of the structure of motives of labor activity” (by T.L. Badoev); “Methodology of motivation for success” (by T. Ehlers); “Job Satisfaction Questionnaire”, JSS (by P. Spector); “Minnesota Satisfaction Questionnaire”, MSQ; Organizational Commitment Questionnaire, OCQ (by L. Porter); “Career Anchors” questionnaire (by Edgar H. Schein). Results. The results revealed that there are a lot of indicators affecting internal affairs employees’ satisfaction with their professional service activities. Conclusions. The development of professional success and efficiency in internal affairs employees requires taking into account the indicators affecting their satisfaction with their professional service activities, among which there are the objective ones: gender, area of service activity, education level and leadership position; and the subjective ones: motivation for success, job satisfaction, career orientation, organizational loyalty. Nature of work and relationships with colleagues play the primary role in internal affairs employees’ satisfaction with their service activities. The most pronounced career orientation is “serving” and stability of the workplace (service).